you need to take (x-3) as a factor of x^2+5x-30
(x-3)(x+8) = x^2 +5x -24 so you have to -6 to get your original so in the same way as long division of numbers you have (x+8) lots of (x-3) remainder -6 so the solution is (I think!) (x+8) -6/(x-3)
2006-10-11 09:37:37
·
answer #1
·
answered by Gina7 1
·
0⤊
0⤋
Don't divide, combine. I'm assuming x*2 meant x^2
I'm also assuming it was = 0
x^2+5x-30 + x - 3
x^2 + 6x - 33 = 0
x = -9.48 or x = 3.48
2006-10-11 09:35:32
·
answer #2
·
answered by Mariko 4
·
0⤊
0⤋
(x^2 + 5x - 30) + (x - 3) = x^2 + 6x -33
Unless you meant:
(x^2 + 5x - 30) + (x - 3) = 0
x^2 + 6x - 33 = 0
x = [-6 +/- sqrt(6^2 - 4*1*(-33))]/2
x = 3.48 or -9.48
2006-10-11 09:40:11
·
answer #3
·
answered by T 5
·
0⤊
0⤋
Well, what does the equation equal to? Does it equal to "x"? Zero? In order to find a variable (in this case, x) the equation needs to be complete.
2006-10-11 09:38:22
·
answer #4
·
answered by ixion151 1
·
0⤊
0⤋
............1.....8
1 -3 / 1 5 -30
..........1 -3
..........----------
..............8 -30
..............8 -24
..........----------
...................-6
So the answer is
x+8 remainder -6 / (x-3)
2006-10-11 09:37:03
·
answer #5
·
answered by Puzzling 7
·
0⤊
0⤋
this is wat im assuming...
x^2+5x-30 + x - 3
x^2 + 6x - 33 = 0
x = -9.48 or x = 3.48
2006-10-11 09:46:11
·
answer #6
·
answered by avant1991 3
·
0⤊
0⤋